MODERN APPROACHES TO THE CREATION OF SELF-DETERMINING MACHINE INTELLIGENCE: THE PHILOSOPHICAL ASPECT - Karpenko, Vitaliy Ye. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2018)
The article explores the philosophical aspect of the basic approaches to the creation of selfdetermining machine intelligence. The problem of understanding machine intelligence appears for modern philosophy as a complex and multidimensional task. One of the most controversial issues in this context is hypothetical future of self-determining machine intelligence. Very topical at the same time are various transhumanist ideas. These ideas express concern for a certain good, although in their specific understanding. It refers to the benefit for both the modern man and those who are considered as other forms of human being (transhumans, posthumans, etc.). In the course of mutual enrichment of concepts that denote different directions of computerization and transhumanism, something qualitatively new arises: the concept of self-determining machine intelligence in its modern form. However, a complete description and an adequate understanding of this type of intelligence is a super complicated task. In this case, it is required to create a common “metamodel”, which “promises” the achievement of the goal (ie, successful modeling). Such a “metamodel” should consistently generate relevant research problems for more specific studies. But at a certain stage it can turn out to be one of those “paradigms” that, as T. S. Kuhn wrote, stopped generating research problems and instead turned into the “tools” of engineering disciplines. Therefore, it should be noted that denying the importance of responding to possible threats at the level of a common “metamodel” can provide a precedent for non-response for any other “less hypothetical” danger. An adequate methodological principle for solving this problem is the precautionary principle. According to this principle, the scientific community and society must move towards one common goal. This means that it is necessary to eliminate fears of society about the dangerous prospects of scientific and technological growth, popularize scientific knowledge, overcome myths that non-specialists associate with science. It is necessary to create reserves to answer the permissible, and not only confidently predicted threats. These reserves are created not only in the course of scientific research, but also through the humanization of science and society, the humanization of the human mentality itself. Only on this basis the ability of society to respond adequately to crisis situations can be made.